The influence of H2AX and γH2AX on chromatin condensation - Norskog, Sarah Samaya, author; Hansen, Jeffrey, advisor; Luger, Karolin, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2010)
Chromatin composition and structure are essential for the condensation of the genome and the regulation of a wide range of cellular activities. Chromatin condensation is thought to be controlled predominantly through interactions mediated by the unstructured amino terminal domains of the core histones H4, H3, H2A and H2B. In addition to the amino terminal domain, histone H2A contains an unstructured carboxyl terminal domain. Multiple H2A variants, many differing from major type H2A in this C-terminal domain sequence, have been identified. The most studied of variant is H2AX, which contains a conserved serine residue that becomes phosphorylated following double strand DNA breakage (yH2AX). Although the phosphorylation of the H2AX has been identified as a key step in major genomic activities, the basic mechanism by which it functions remains controversial. Here, I have determined the structural role of H2AX and yH2AX using in vitro assays which utilize defined nucleosomal arrays. H2AX and yH2AX alter chromatin folding under high salt concentrations but show no discernable differences in low concentrations of salt or under conditions which favor oligomerization. The phosphorylation of H2AX does not alter the folding or oligomerization relative to the unphosphorylated form, indicating yH2AX more likely functions as a signaling and recruitment motif rather than as a chromatin secondary structure remodeling factor.
Covers not scanned.
Keywords: Chromatin; Histones